(untitled) (European Journal of Formal Sciences and Engineering, 2021)
The article studies the properties of interior color schemes and finishing materials in order to find optimal combination for improving indoor conditions in higher education study room and to contribute to better educational process. Optical, physical, physiological and emotional properties of colors and materials are compared to living and study requirements in the context of their complexity. Recommendations for appropriate combinations of finishing materials and colors are given.